Analysis Efficiency Of 3 Phase AC Motor Use A Centrifugal Pump Drive On The Water Tower Of PDAM Tirtanadi, North Sumatra - Kukuh Pambudi; Amani Darma Tarigan; Hamdani Hamdani (Jurnal Scientia, 2024)
This paper described an examines the efficiency of a 3-phase alternating current (AC) motor utilized to power a centrifugal pump at the water tower operated by PDAM Tirtanadi in North Sumatra. The primary objective is to assess the performance and energy efficiency of the motor-pump system, which is critical for ensuring optimal water supply management and minimizing operational costs. The research involves detailed data collection on the electrical consumption and output performance of the 3-phase AC motor during its operation. Parameters such as voltage, current, power factor, and load conditions are measured and analyzed. The efficiency of the motor is evaluated based on its ability to convert electrical energy into mechanical energy to drive the centrifugal pump effectively. Findings from this study reveal key insights into the operational efficiency of the 3-phase AC motor under varying load conditions. The analysis indicates the factors that influence motor efficiency, including mechanical losses, electrical losses, and the alignment of the motor with the pump's operational requirements. The study concludes with recommendations for optimizing motor efficiency, which include regular maintenance schedules, appropriate motor sizing, and potential upgrades to more energy-efficient motor models. Implementing these recommendations could lead to significant energy savings and improved performance of the water supply system managed by PDAM Tirtanadi. Overall, this research highlights the importance of continuous monitoring and evaluation of motor-driven pump systems in water supply infrastructure to achieve sustainable and cost-effective operations.